2016
DOI: 10.1016/j.psychres.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Discriminability of personality profiles in isolated and Co-morbid marijuana and nicotine users

Abstract: Specific personality traits have been linked with substance use disorders (SUDs), genetic mechanisms, and brain systems. Thus, determining the specificity of personality traits to types of SUD can advance the field towards defining SUD endophenotypes as well as understanding the brain systems involved for the development of novel treatments. Disentangling these factors is particularly important in highly co-morbid SUDs, such as marijuana and nicotine use, so treatment can occur effectively for both. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…4 Our survey of the literature reveals several other studies wherein control samples produced trait scores different from the NEO-FFI sample. 32,33 One possible explanation is that there was something unique about the control samples in these studies. Generally, slightly higher conscientiousness, extraversion, and agreeableness, and lower neuroticism has been noted in research volunteers, suggesting a motivation, congeniality, and confidence in those participating in studies.…”
Section: Discussionmentioning
confidence: 94%
“…4 Our survey of the literature reveals several other studies wherein control samples produced trait scores different from the NEO-FFI sample. 32,33 One possible explanation is that there was something unique about the control samples in these studies. Generally, slightly higher conscientiousness, extraversion, and agreeableness, and lower neuroticism has been noted in research volunteers, suggesting a motivation, congeniality, and confidence in those participating in studies.…”
Section: Discussionmentioning
confidence: 94%
“…These include male sex, early exposure to traumatic events, early use initiation, family history of substance use, childhood depression, and conduct disorder symptoms ( Gray and Squeglia, 2018 , Meier et al, 2016 , Tomko et al, 2019 ). High impulsivity and certain personality traits are also associated with the disorders ( Beaton et al, 2014 , Ketcherside et al, 2016 ). In particular, work by co-author Filbey’s lab showed that openness distinguishes cannabis-only users from nicotine-only users, co-morbid marijuana and nicotine users, and non-users ( Ketcherside et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…High impulsivity and certain personality traits are also associated with the disorders ( Beaton et al, 2014 , Ketcherside et al, 2016 ). In particular, work by co-author Filbey’s lab showed that openness distinguishes cannabis-only users from nicotine-only users, co-morbid marijuana and nicotine users, and non-users ( Ketcherside et al, 2016 ). The results from this study also indicate that conscientiousness is lower among cannabis users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraversion is a good predictor of the tendency of students to drug abuse, according to the findings of this study [37]. Examining the factors associated with drug use has shown that personality characteristics are among the most important predictors of the use of various substances, such as cigarettes, alcohol, and drugs [38].…”
Section: Discussionmentioning
confidence: 64%